Penerapan Model Two Stay Two Stray Berbantuan Alat Peraga Dakon Untuk Meningkatkan Hasil Belajar Matematika Siswa SD - Bertha, Bertha (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The use of traditional game media has the potential to be used in mathematics learning. This study aims to improve the quality of the process and learning outcomes of fifth-grade students at State Elementary School of 14 Teminabuan, South Sorong, West Papua on the competence of Highest Common Factor (HCF) and Lowest Common Multiple (LCM) through the application of the Two Stay Two Stray learning model assisted by the Dakon teaching aids. The type of research conducted is classroom action research (CAR). This research was carried out in 2 cycles, each cycle consisting of 4 stages, namely: planning, observing, implementing, and reflecting. The increase in students' understanding of the Highest Common Factor (HCF) and Lowest Common Multiple (LCM) concepts was higher after receiving learning by applying the Two Stay Two Stray model with the aid of Dakon props than the understanding of students who received conventional learning model. There is a tendency to increase student activity in the learning process after receiving the Two Stay Two Stray model learning aided by the Dakon props in Cycle II than the student activity in the pre-action and Cycle I which received teacher-centered learning.